Billy Cash: Digital piggy bank for meaningful saving behavior - De Francisco Vela, Santiago; Casais, Mafalda (RChD: creación y pensamiento, 2018)
Virtue is a fundamental aspect of well-being. Past research has proposed that emotional-driven design can be a powerful mediator towards supporting virtue. However, virtue-focused solutions generally target isolated actions. Here, using saving as an example of virtuous behavior we present a design cas —Billy Cash, a digital piggy bank that allows users to reflect during the saving process and extend the appreciation of the purchased item—that aims to demonstrate how design can facilitate virtuous behavior that is sustainable and can promote actual change. Through the analysis and evaluation of the design case, we propose a framework of design for virtuous behavior. The framework sets a scenario for design interventions that contemplate virtuous actions to be transformed into virtuous behaviors mediated by the resignification of resources and stimuli behind the experience.